Jeremiasz – prorok osaczony - EPSTEIN, Rav Daniel; GROSFELD, Jan (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2011)
Rav Daniel Epstein, Jewish philosopher, profound interpreter of the Torah and expert in the Talmud, takes the example of Jeremiah in order to describe the nature of the mission and the personal experience of a prophet. Jeremiah personifies and expresses the condition of the Jewish people and of their particular relation with God. According to the author, the characteristic features of the Jewish lot and of the Jewish history are lamentations and moaning. The fact of being chosen by God inevitably inflicts suffering: Jeremiah’s mission is like a burning fire. Suffering is first inflicted on him by his own people, as his mission is not welcome by them. He is mediator between God and the Israelites, as well as mediator between the Israelites and God. Jeremiah attempts his own interpretation of the events and it is in their light that he can see more fully who God is. Epstein sees the Biblical story also in relation to the lives of the Jews in the present times. By drawing on the examples taken from his own life and from the life of his family, he gives special witness to the truth inherent in the Torah and in the Talmud. While showing the suffering of the Jewish people, he never confines himself to its description, but always perceives it in the context of hope. Against all appearances, Jeremiah is not a prophet of unhappiness, but a prophet of joy. Summarized by Jan Grosfeld Translated by Dorota Chabrajska